Kajian Pengaruh Konfigurasi Mesin Penggilingan terhadap Rendemen dan Susut Giling beberapa Varietas Padi - Rokhani Hasbullah; Anggitha Ratri Dewi (PERTETA, 2009)
Rice is the staple food for Indonesian people so that the rice supply will be the barometer for thenational’s food security. In rice production, both of postharvest losses and low milling yield are still theproblems due to lack of postharvest handling. In this study, the effect of rice milling machine configurationon the milling yield and quality of some paddy varieties was examined. Paddy variety of Ciherang, Cibogoand Hybrid were milled using a configuration process of: 1) two husking and two polishing (2H-2P), 2) onehusking, one separating and one polishing (H-S-P), and 3) one husking, two separating and two polishing(H-2S-2P). The results show that the paddy varieties significanly affect milling yield and losses. However,rice milling machine configurations are not significantly affect the milling yield and losses. Paddy variety ofCibogo resulting in the highest milling yield (67.80 %) compared to Ciherang (62.61 %) and Hibrida (60.78%). Paddy variety of Cibogo resulting in the lowest losses (1.41 %) compared to Ciherang (3.43 %) andHibrida (3.03 %). The speed of milling process for configuration of 2H-2P, H-S-P and H-2S-2P were 228.1kg/hour, 295.6 kg/h and 263.2 kg/hr respectively.Keywords: paddy, rice milling configuration, milling lossess, milling yieldDiterima: 30 Juni 2009; Disetujui: 19 Oktober 2009